Investment, Inflation and Economic Growth Nexus (The Pakistan Development Review, 2009)
The paper has twofold objectives. Firstly, the impact of the inflation rate on economic growth with the possibility of two threshold levels for Pakistan using annual data from 1961 to 2008 is examined and secondly, nonlinear relationship between inflation and investment has been investigated. Inflation and growth models support the existence of a nonlinear relationship with two thresholds (6 percent and 11 percent). Inflation below the first threshold affects economic growth positively but insignificantly; at moderate rates of inflation, between the two threshold levels, the effect of inflation is significant and strongly negative and at high rates of inflation, above the second threshold, the marginal impact of additional inflation on economic growth diminishes but is still significantly negative. Investment is one of the possible channels through which inflation influences economic growth and the analysis indicates the nonlinear relationship between these two variables with only one threshold at 7 percent. Rate of inflation below the threshold level has positive but insignificant impact, while above the threshold it has strong negative and significant impact on the investment. Therefore, it is desirable to keep the inflation below 6 percent because it may be helpful for the achievement of robust economic growth and investment. JEL classification: E22, E31, O40 Keywords: Investment, Inflation, Economic Growth, Nonlinear, Pakistan.